2018
DOI: 10.1177/0022242918809930
|View full text |Cite
|
Sign up to set email alerts
|

Creating Effective Online Customer Experiences

Abstract: Creating effective online customer experiences through well-designed product web pages is critical to success in online retailing. How such web pages should look specifically, however, remains unclear. Previous work has only addressed a few online design elements in isolation, without accounting for the potential need to adjust experiences to reflect the characteristics of the products or brands being sold. Across 16 experiments, this research investigates how 13 unique design elements shape four dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
332
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(362 citation statements)
references
References 77 publications
14
332
0
16
Order By: Relevance
“…Chen et al (2017) point out that retailers can establish relational capital with purchasers by improving mutual trust, cooperation, and appreciation with them. Bleier et al (2019) find that a manufactured item's type and brand reliability influence the effect of each experience aspect on end users' purchase decisions. Sullivan and Kim (2018) indicate that perceived value affects the experiences of online trust among purchasers and their commitment to buy again from the same website.…”
Section: Effects Of Perceived Risk On Purchase Intention In Social Comentioning
confidence: 91%
“…Chen et al (2017) point out that retailers can establish relational capital with purchasers by improving mutual trust, cooperation, and appreciation with them. Bleier et al (2019) find that a manufactured item's type and brand reliability influence the effect of each experience aspect on end users' purchase decisions. Sullivan and Kim (2018) indicate that perceived value affects the experiences of online trust among purchasers and their commitment to buy again from the same website.…”
Section: Effects Of Perceived Risk On Purchase Intention In Social Comentioning
confidence: 91%
“…Third, anthropomorphism also increases social presence, defined as the degree to which a communication medium allows one to perceive the communicator as being psychologically present during an interaction (Short, Williams, & Christie, 1976). Social presence resulting from anthropomorphization has been associated with trust, engagement, and satisfaction (Kumar & Benbasat, 2006;Picard, 1997;Qiu & Benbasat, 2009;Turkle, 2017;Bleier, Harmeling, & Palmatier 2019). In examining specific anthropomorphic features, researchers have shown that certain personality characteristics such as friendliness and expertise (Verhagen et al, 2014) as well as embodiment and communication style (Qiu & Benbasat, 2009) influence perceptions of social presence.…”
Section: Encouraging Voluntary Self-disclosure With Conversational Agmentioning
confidence: 99%
“…The development of communication technologies has resulted in online brands that bring online brand experiences to customers (Ha and Perks, 2005;Morgan-Thomas and Veloutsou, 2013;Lee and Jeong, 2014). Providing an exceptional brand experience in an online context is critical due to the energetic flow of information describing this distinctive electronic environment (Morgan-Thomas and Veloutsou, 2013; Lee and Jeong, 2014;Bleier et al, 2019).…”
Section: Online Brand Experiencementioning
confidence: 99%